Transverse fatigue behaviour and residual stress analyses of double sided FSW aluminium alloy joints - Salvati, E; Everaerts, J; Kageyama, K; Korsunsky, A (Wiley, 2019)
Friction stir welding (FSW) since its invention has been attracting relevant interest for joining aluminium alloys. Due to the nature of this process, the materials can be joint without melting. Thanks to this peculiar characteristic, the issues associated with the cooling from liquid phase are avoided or considerably reduced, such as cracking, porosity, and defects. However, as well as other well-established welding techniques, the FSW process gives rise to formation of residual stress in the welding region and surrounding volume: heat and thermo-mechanical affected zones. Presence of residual stress in a mechanical component is well-known to affect its performance, particularly regarding fatigue at high number of cycles. Another aspect that influences the fatigue life is the underlying microstructure. In this work, we firstly study the residual stress field and the underlying microstructural features arising in FSW butt joints and their effect on the fatigue performance of this type of weldments. The evaluation of residual stress field is carried out by means of modern experimental techniques. In the first instance, synchrotron X-ray powder diffraction was employed for two-dimensional full field maps of residual stress. Corroboration of these measurements was done by exploiting the capability of focused ion beam and digital image correlation (FIB-DIC), which is able to deliver pointwise absolute measurement of residual stress. A set of FSW samples were then tested under uniaxial fatigue loading at several loading ranges, in the high cycle fatigue regime, in order to understand whether the severity of loads affects the crack path and life endurance. Fractographic and electron backscattered diffraction (EBSD) analysis then revealed crack nucleation site and propagation mechanisms with the respect of the underlying microstructure. Outcome of these experimental studies is then thoroughly discussed.